2020
DOI: 10.1101/2020.11.15.383695
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Role of BMP signaling during early development of the annelidCapitella teleta

Abstract: The mechanisms regulating nervous system development are still unknown for a wide variety of taxa. In insects and vertebrates, bone morphogenetic protein (BMP) signaling is known to play a key role in both neural specification and dorsal-ventral (D-V) axis formation, leading to speculation about the conserved evolution of nervous systems. Studies outside insects and vertebrates show a more diverse picture of what, if any role, BMP signaling plays in neural development across Bilateria. This is especially true … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 88 publications
0
6
0
Order By: Relevance
“…While the DV patterning mechanism is considered conserved across bilaterian clades (12), investigations on several spiralian representatives have revealed different results (13)(14)(15)(16)(17)(18). Meanwhile, in various spiralian phyla, DV patterning is deeply integrated into a highly specialized organizer-driven developmental mode (23,(26)(27)(28)(29), with the underlying molecular mechanism largely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…While the DV patterning mechanism is considered conserved across bilaterian clades (12), investigations on several spiralian representatives have revealed different results (13)(14)(15)(16)(17)(18). Meanwhile, in various spiralian phyla, DV patterning is deeply integrated into a highly specialized organizer-driven developmental mode (23,(26)(27)(28)(29), with the underlying molecular mechanism largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A major issue in the studies of spiralian DV patterning is that researchers have reported very different results using different systems. Researchers concluded that spiralian DV patterning relies on bmp2/4 (without known roles of chordin) (19,20), other BMP ligand and antagonist (13), or even non-BMP signaling (14)(15)(16)(17)(18). Taken together, a paradox rises: while it is widely accepted that the common ancestor of bilaterians utilizes bmp2/4 and chordin for DV patterning (12), this character is not revealed in the six spiralian representatives spanning three spiralian phyla (three annelids, two mollusks and one platyhelminth, Fig.…”
Section: Goshimai DV Patterning Relies On Bmp2/4 and Chordinmentioning
confidence: 99%
See 3 more Smart Citations